2022
DOI: 10.21787/jbp.14.2022.31-41
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Models in the Theory of Planned Behavior to Predict Whistleblowing Intention

Abstract: The low rank of Indonesia's Corruption Perception Index (CPI) 2021 indicates that government fraud is still a significant problem. One improvement in bureaucracy reform is the whistleblowing system to report wrongdoing. Although this system is applicable, the effectiveness of whistleblowing as a mechanism to detect fraud depends on the willingness of an employee to report misconduct. As a part of government management systems in local government, the internal auditor has a unique position to detect fraud as ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Moreover, it points out the nuanced impact of social anxiety, locus of control, cultural dimensions, and personal beliefs on whistleblowing decisions. Advocating for improved whistleblower protection and secure, anonymous reporting avenues, the research aligns with efforts to combat corruption by promoting ethical behavior within organizations, as echoed by Berendt & Schiffner (2022);and Hamdani & Hariadi, (2022), who stress the importance of digital safeguards in e-Government systems.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, it points out the nuanced impact of social anxiety, locus of control, cultural dimensions, and personal beliefs on whistleblowing decisions. Advocating for improved whistleblower protection and secure, anonymous reporting avenues, the research aligns with efforts to combat corruption by promoting ethical behavior within organizations, as echoed by Berendt & Schiffner (2022);and Hamdani & Hariadi, (2022), who stress the importance of digital safeguards in e-Government systems.…”
Section: Discussionmentioning
confidence: 96%
“…The recent survey found that 42% of fraud detections are attributed to whistleblowing, surpassing internal audits and management reviews (ACFE, 2022). Within the public sector accounting context, the critical role of accountants and auditors in uncovering and reporting accounting fraud has been increasingly recognized, as highlighted by (L. Gao & Brink, 2017;Hamdani & Hariadi, 2022).…”
Section: Introductionmentioning
confidence: 99%